(untitled) (Педагогіка вищої та середньої школи, 2007)
The given article represents some aspects of the musical education in the second half of the XVIII th and in first half of XIX th centuries. The organizing of the musical education continued the stated traditions in sing the best achievements of national and world music culture. Different forms and methods of music-aesthetic upbringing of the youth were used with the aim of forming a personality and professional training of a teacher of Music.